Algas marinas bentónicas de Todos Santos, Baja California Sur, México - Mateo-Cid, Luz Elena; Mendoza-Gonzalez, A. Catalina (Instituto de Ecología, A.C., 1994)
Results are presented of a study on benthic marine algae from the tropical waters of the coast of Todos Santos, Baja California Sur, during 1989. The floristic list includes data on the species found, the state of reproduction, mode and epiphytism. Five taxa of Cyanophyceae, 69 of Rhodophyceae, 20 of Phaeophyceae, 8 of Bacillariophyceae and 15 of Chlorophyceae were identified. The algal flora of Todos Santos is tropical and greater diversity was found in fall and winter than in spring and summer. The Rhodophyceae are dominant in terms of diversity. Species diversity in relation to temperature, currents and tides is also discussed.